Elastocaloric cooling potential of NiTi, Ni2FeGa, and CoNiAl. (1st September 2015) - Pataky, Garrett J.; Ertekin, Elif; Sehitoglu, Huseyin
Abstract: Solid state elastocaloric cooling, the endothermic reversible martensitic phase transformation in shape memory alloys, has the potential to replace vapor compression refrigeration. NiTi, Ni2 FeGa, and CoNiAl shape memory alloys were experimentally investigated to measure the magnitude of temperature change using thermography during uniaxial tensile experiments. Consecutive tensile cycles were also performed, and they revealed a symmetric temperature profile between the two cycles. The unique, dual camera technique of digital image correlation and thermography was utilized to track the transformation bands and temperature gradients to gain insight about the unloading, endothermic process. Fatigue implications, elevated temperature environments, and the theoretical maximum temperature based on entropy change were discussed.